Peran Organisasi Internal Kampus dalam Meningkatkan Prestasi Dan Kemampuan Komunikasi Mahasiswa Di STIT Palapa Nusantara Lombok-NTB - Nasrullah; Muhammad Hanafi; Sukranudin (Pendidikan Al-Gafari, 2024)
Students as part of a society that has a mark plus separately own a very important role in the growth and development of the nation. Where are the students? Of course, no one will once be free from life and social society, this makes the student not quite enough answer separately regarding their education travel because they are capable apply their knowledge get on the bench studying to help existing problems in public. The study aims to find a description of the role of internal campus organizations in increasing achievements and abilities of communication with students at the STIT Palapa Nusantara Lombok-NTB campus. Where are the internal campus organizations? Of course, just expected will bring a big impact on the development campus and share existing students, however the facts that happened in the field show that the internal campus organization at STIT Palapa Nusantara still has minimal movement, the reason is is lack of support and motivation from party campus and students alone in various their activities held. Studying this uses a approach qualitative, which is of a nature natural and more put forward feelings or experiences experienced by the source of the data. With method study studies case, that is something research conducted to learn something problems that occur in something group. Subject, his research is on administrator student organizations active organization and throughout student active various majors at STIT Palapa Nusantara Lombok-NTB. The procedure used in the study is interviews and observations, then after the data is collected analyzed using stages that are data presentation and withdrawal conclusion. Based on the results of research that has been done, the conclusion from the study is that the role of internal campus organizations in increasing achievements and abilities of communication students at STIT Palapa Nusantara Lombok-NTB still not yet been achieved, based on results of interviews that have been obtained several factors become trigger matter these, among others is lack of support from party campus and lecturers, lack interest student follow activities that have been provided, up to lack of awareness every administrator organization to roles and responsibilities answer each existing division.